2008
DOI: 10.1002/eji.200838535
|View full text |Cite
|
Sign up to set email alerts
|

Induction, function and regulation of IL‐17‐producing T cells

Abstract: Recent reports have provided convincing evidence that IL-17-producing T cells play a key role in the pathogenesis of organ-specific autoimmune diseases, a function previously attributed exclusively to IFN-c-secreting Th1 cells. Furthermore, it appears that IL-17-producing T cells can also function with Th1 cells to mediate protective immunity to pathogens. Although much of the focus has been on IL-17-secreting CD4 1 T cells, termed The main function of IL-17-secreting T cells is to mediate inflammation, by sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
240
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(254 citation statements)
references
References 113 publications
11
240
0
2
Order By: Relevance
“…1,11,12 In contrast, IFN-c is thought to inhibit Th17 immune responses. 30 As the effect of the presence or absence of IL-10 in the proinflammatory pattern was observed at 48 hpi, without significant changes in the frequency of T cells, it is likely that IL-10 is required for the proper secretion of cytokines by innate and epithelial cells, which will in turn promote a Th17 response profile. 30 Our data show that the lack of IL-10 during S. pneumoniae infection, leads to higher levels of IFN-c and TNF-a, which might inhibit the development of Th17 immune responses and lead to an exacerbated innate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,12 In contrast, IFN-c is thought to inhibit Th17 immune responses. 30 As the effect of the presence or absence of IL-10 in the proinflammatory pattern was observed at 48 hpi, without significant changes in the frequency of T cells, it is likely that IL-10 is required for the proper secretion of cytokines by innate and epithelial cells, which will in turn promote a Th17 response profile. 30 Our data show that the lack of IL-10 during S. pneumoniae infection, leads to higher levels of IFN-c and TNF-a, which might inhibit the development of Th17 immune responses and lead to an exacerbated innate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of Th1 and Th17 responses in HCVinfected individuals was studied, and it was reported that TGF-β and IL-6 promote differentiation of naive murine CD4 + T cells into IL-17-secreting Th17 cells. In addition, it has been reported that other innate cytokines, including IL-1, IL-23, TNF-α, and IL-21, in different combinations or with TGF-β, are also involved in differentiation, amplification, or stabilization of the Th17 phenotype [17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of interleukin 17 nitrite oxide synthase (iNOS) can produce nitrite oxide [11]. It also stimulates production of pro inflammatory cytokines (TNF-alpha, IL-1-beta), inflammatory chemokines to elevation of phagocytosis and effect on neutrophils and macrophages [12,13]. Neutrophils in leishmaniasis are very important in remove of parasites [13], but its short life cause serve only as "Trojan Horse" to avoid destruction by immune system [14].…”
Section: Introductionmentioning
confidence: 99%